Shared Context for Engineering Students Learning Business - Leung, Chi Hong; Pang, Elvy (Asian Journal of Empirical Research, 2017)
The shared context is a learning environment in which knowledge sharing is promoted by communication and collaboration among students. This engages students in any learning activity using cooperation, evaluation and interaction to build knowledge socially when coming across disagreement and difference. The communication technologies make it possible for everyone to contribute to the online community for sharing knowledge. The paper discusses the theoretical framework and then provides an example illustrating how to design teaching and learning activities to cultivate the sharing culture in classes with both engineering and business students. Business people tend to be extroverted while engineers are usually introverted. There are usually communication barriers among students from these two disciplines studying in the same subject. A survey was conducted to investigate students’ attitudes to the shared context and results suggest that this can integrate the higher learning motivation into the physical interactions and communications among peers. It encourages knowledge sharing through socialization – an important step towards knowledge creation – in both the online and real worlds. The shared context is effective when it integrates with different skills and interests of students who provide diversity into the traditional classroom learning. This makes knowledge possible to be accumulated, examined, revised and distributed.